BRAVOSEIS Onshore Seismic Array ... - Heit, B.; Yuan, X.; Almendros, J.; Abella, R.; Carmona, E.; Aguí, F.; Carrión, P. (GFZ Data Services, 2020)
The Bransfield Strait is a seismically active extensional rift located between the Antarctic Peninsula and the South Shetland Islands. The Strait is partly located on continental crust including areas within the transition to seafloor spreading. The amphibious seismic network BRAVOSEIS is an international effort focused on the seismological research of submarine volcanoes and rift dynamics in the Bransfield Strait. This network is the onshore component of the entire network consisting of 15 broadband land stations deployed in the South Shetland Islands and Antarctic Peninsula between January 2018 and February 2020. The offshore components (network code ZX) include 9 broadband ocean bottom seismometers (OBS) across the Central Bransfield Basin and a group of 6 hydrophone moorings spanning the rift area of 200 x 100 km2, with inter-station distance of ~30 km. Additionally, a smaller offshore array consisting of 15 short-period OBSs with an aperture of 20 km and a narrow inter-station distance of ~4 km was ...